Поверхнева енергія захисно-живильних розчинів як фактор впливу на ефективність обробки об’єктів рослинного походження - Іноземцев, Г. Б.; Окушко, О. В. (Енергетика і автоматика, 2017)
SURFACE ENERGY OF PROTECTIVE-NUTRITIVE SOLUTIONS AS A FACTOR OF INFLUENCE ON EFFICIENCY OF PROCESSING OF OBJECTS OF PLANT ORIGING.B. Inozemtsev, O.V. Okushko An analysis of the achievements of modern science in the field of electrotechnology shows that they by their functional indicators significantly outperform the traditional ones, including in the processes of nutrition and protection of cultivated plants.Recently, widespread use in these processes is an induction method of spraying various types of solutions (nutritious, sweeping, mineral fertilizers, etc.), the expediency of using it as a conveyor of solutions to plants, confirms its advantages - reducing the losses of solutions, obtaining a high level of dispersion them, an increase in the coefficient of deposition on the green mass of processing objects, especially on the reverse of their surfaces.The purpose of the research is to develop technical and technological measures to increase the efficiency of the induction method by changing the surface energy and optimizing the modes of application of protective and nutrient solutions in crop production.Materials and methods of research. In the course of our research, including conditions of production, it was obtained convincing evidence of the need for adjustments in the direction of increasing the effectiveness of the process of applying protective and nutritional solutions by induction.Research results. When conducting research, we drew attention to the fact that in real conditions, with increasing the potential on the charging (coronating) electrode, there is not always an increase in surface energy. This is due to the specificity of the working solutions, which are aqueous solutions, which determines their small bulk resistance (≤ 103 Ohm  cm), electric charge loss.